The Lecture and its Infelicities: Recovering Goffman's Legacy for (Mis)Performance Studies - Čale Feldman, Lada (2009)
The paper redefines Goffman's legacy for performance studies, arguing in favor of a return to his deconstructive social poetics. A particular case in point is his lecture on "the lecture", a written performance piece that blurs the line between writing and speech, making his readers return to the very occasion in which the lecture was delivered.
Projekt MZOS
ENG